Adoption of the CSD Matrix to Improve the Business Process Quality of Software Development Teams - Nabila Putri Ocktavia; Beni Suranto; Chanifah Indah Ratnasari (bit-Tech, 2025)
This research aims to improve the quality of business processes in software development teams through the application of the CSD Matrix method. The CSD Matrix was reformulated in this research as a visual decision support tool to improve early sprint planning, by mapping project elements into three categories: certainties, suppositions, and doubts. The method was applied to the software engineering team at Mamikos through the completion of Capability Maturity Model Integration (CMMI) indicator-based questionnaires, both before (pre-test) and after (post-test) implementation. The results showed a significant improvement in the process maturity level, from an average score of 2.70 (Level 2: Developing) to 4.20 (Level 4: Managed), especially in the areas of retrospective, requirements management, and onboarding. This finding confirms that the CSD Matrix is able to encourage the structuring of the planning process, strengthen the team's collective awareness of risks and assumptions, and improve the effectiveness of cross-functional communication. With its lightweight, visual, and adaptive characteristics to Agile work environments, CSD Matrix proves to be a practical approach that can fill the gap between formal documentation and the daily coordination needs of software development teams.